APPLICATION OF THE CIRC LEARNING MODEL TO IMPROVE STUDENT LEARNING RESULTS ON HISTORICAL TEXT MATERIAL IN CLASS XII MIPA 1 SMA NEGERI 1 MOJOSARI - Susiani Susiani (Jurnal Scientia, 2022)
This research is a class action research conducted based on the fact that the learning outcomes of students in class XII MIPA 1 SMA Negeri 1 Mojosari are still under the KKM. This study aims to determine the increase in student learning outcomes in historical text material through the application of the Cooperative Integrated Reading and Composition (CIRC) learning model . The research was carried out for two cycles with stages consisting of planning, implementing, observing and reflecting. The results showed that learning with the CIRC model had a positive impact on improving student learning outcomes which was marked by an increase in student mastery in each cycle, namely cycle I (72.73%) and cycle II (87.88%). In the aspect of student activity also shows remaining active in learning and in the aspect of the implementation of lesson plans shows learning is in the good category, namely in the first cycle it gets an average score of 3.3 (good) and increases to 3.5 (good) in the second cycle and the implementation reached 100%. The application of the CIRC model has a positive effect, namely it can increase student learning motivation as indicated by the average student answers which state that students are interested and interested in the CIRC model so that they become motivated to learn.